Contribution to the phytotherapy against scorpion sting envenomation in the Naama region (Algeria) - Boucherit, Hafidha; Benabdeli, Khéloufi; Benaradj, Abdelkrim (Lazaroa, 2017)
Scorpion envenomation represents one of the most important public health problems in Algeria and particularly in the High Plateaus and the South regions. Every year, several thousand people are stung by scorpion and an average of one hundred die. In the region of Naama, nearly 1500 people are bitten annually; mainly at the beginning and at the end of the summer period; and, on the average, three die from the consequences of these bites. The study is prospective and was carried out over a period of three months between December 2015 and February 2016. It is based on a survey supported by fifty questionnaires for the population and herbalists in the Naama region. Results showed that the most widely used plant species was Hammada scoparia, commonly known as "Remt", with a percentage of 74%, much higher than the rest of used plants in the area and it should be studied in detail. One teaspoon of Hammada scoparia powder combined with a tablespoon of pure butter (from ovine milk for instance) and cooked at low heat is the most used remedy. 50% of the surveyed people answers they are convinced this treatment is the most efficient to have all active compounds of the species.